A Single Case Study in Management of Pakshaghat with Ayurveda - Mishra, Reena Shivasgar; Chandurkar, Vivek (International Research Journal of Ayurveda & Yoga, 2024)
In the Sharira, Vata is seen as the controller of all things. Vatavyadhi is the term for the influence of vitiated vata on the Dusyas, which permeate the whole body or a portion of it and give rise to various sorts of illness. One of the significant illnesses that fits this description is pakshaghata, also referred to as hemiplegia. One Vataj Nanatmaja Vyadhi who is regarded as a Mahavatavyadhi is Pakshaghata. There is a correlation between pakshaghata and hemiplegia, a condition caused by a cerebrovascular accident or stroke. Hemiplegia, which results in both mental and physical instability. In the world’s population, there are around 9 instances per 1000 people. A stroke is described as an abrupt onset of vascular mechanism-related neurologic impairment. 15% are initial hemorrhages, and 85% are ischemic. The World Health Organization estimates that 15 million stroke victims globally experience a stroke each year, of whom 5 million die and another 5 million become permanently incapacitated. According to current scientific theory, brain injuries that are too severe for treatment to reverse can result in lifelong neurological impairment. As a result, the prognosis for the illness is dismal, leaving the crippled individual dependent. The current research aims to provide baseline data for student physicians to cope with this terrible condition by identifying the etiopathogenesis, clinical aspects, and therapy of the disease from Ayurvedic classics.